Development of the formulation for extruded products based on sugar corn grain and determining their quality indicators - Dzyuba, Nadya; Bunyak, Elena; Sots, Sergey; Bilenka, Irina (Eastern-European Journal of Enterprise Technologies, 2019)
The formulations of extruded products based on sweet corn grain, bare-grain barley, carrot root crops, and licorice root and collagen hydrolysate have been developed. We determined physical-and-chemical parameters (wettability, digestibility, and microstructure) of the extrudates obtained. The hardware-technological scheme of production and analyzed parameters of wettability and digestibility are presented. The study of the composition of micronutrients showed that consumption of 100 g of «Kukurudzyanka» sticks satisfies the human need for vitamins A and B6 by 76.62 and 75.76 %, respectively, and consumption of 100 g of «Kukurudzyanka+» ‒ by 80 and 79.25 %. The data obtained showed that an increase in temperature and pH of a medium leads to an increase in the wetting ability of the developed sticks by 14...15 % on average. In vitro studies established that the products developed have a rather high degree of digestibility, which reaches 85 %. The obtained data from the study of quality indicators showed that the content of sanitary-indicative microorganisms corresponds to the sanitary-and-hygienic requirements for breakfast cereals at storage for 6 months at a temperature of (15±5) °C and humidity of 70...75 % in polypropylene packaging. The developed products have a high content of protein substances, which is quite important for meeting the needs of a human body nowadays. Consumption of 100 g of sticks will provide a human body with essential amino acids by almost 24.1 % in general. The products presented in the study have a rather high content of basic micronutrients necessary for a human body, namely calcium, phosphorus and potassium. We can recommend the developed extrudates for use by adolescents, children, for diets and consumption of other segments of the population.